2018
DOI: 10.1002/jpen.1466
|View full text |Cite
|
Sign up to set email alerts
|

Time to Full Enteral Feeding for Very Low‐Birth‐Weight Infants Varies Markedly Among Hospitals Worldwide But May Not Be Associated With Incidence of Necrotizing Enterocolitis: The NEOMUNE‐NeoNutriNet Cohort Study

Abstract: Background Transition to enteral feeding is difficult for very low‐birth‐weight (VLBW; ≤1500 g) infants, and optimal nutrition is important for clinical outcomes. Method Data on feeding practices and short‐term clinical outcomes (growth, necrotizing enterocolitis [NEC], mortality) in VLBW infants were collected from 13 neonatal intensive care units (NICUs) in 5 continents (n = 2947). Specifically, 5 NICUs in Guangdong province in China (GD), mainly using formula feeding and slow feeding advancement (n = 1366),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 44 publications
1
50
1
Order By: Relevance
“…Extremely low-birth-weight infants (<1,000 g) represented the most vulnerable cohort in this study and presented less abundance of genus Bifidobacterium , potentially due to several factors including, lengthened antibiotic courses, 39 underdeveloped gut physiology (i.e., poorer gut motility, and thinner mucus layer 40 ), and difficulties in establishing full enteral feeding. 41 Indeed, previous clinical studies have had difficulties evaluating the beneficial effects of supplementation in this at-risk cohort of preterm infants, 42 while others have seen a reduction in LOS but not in NEC. 42 , 43 Notably, although extremely low-birth-weight Bif/Lacto infants had lower Bifidobacterium abundance than those infants weighing 1,000 g, supplementation in our study did enhance levels when compared to control infants.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely low-birth-weight infants (<1,000 g) represented the most vulnerable cohort in this study and presented less abundance of genus Bifidobacterium , potentially due to several factors including, lengthened antibiotic courses, 39 underdeveloped gut physiology (i.e., poorer gut motility, and thinner mucus layer 40 ), and difficulties in establishing full enteral feeding. 41 Indeed, previous clinical studies have had difficulties evaluating the beneficial effects of supplementation in this at-risk cohort of preterm infants, 42 while others have seen a reduction in LOS but not in NEC. 42 , 43 Notably, although extremely low-birth-weight Bif/Lacto infants had lower Bifidobacterium abundance than those infants weighing 1,000 g, supplementation in our study did enhance levels when compared to control infants.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective cohort study was a part of the NEOMUNE study [ 21 ], which was performed in five neonatal intensive care units (NICUs) from 2011 to 2014 in Guangdong province, China. Inclusion criteria were infants inborn or transferred to the NICU within 24 h after birth, < 37 weeks’ gestation and < 1500 g at birth, survived for at least 24 h. Exclusion criteria included major congenital abnormalities or congenital metabolic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…The same study showed no effect on the overall incidence of necrotizing enterocolitis (NEC) (6/61 vs. 5/60), but the number of fatal NEC cases was highest in the rhIGF-1/BP-3 group (3 vs. 0). Generally, NEC is associated with high mortality (20–30%) and occurs in 5–10% of extremely preterm infants within the first weeks of life ( 18 22 ). Despite comprehensive research, in part using animal models, the pathogenesis of NEC remains ambiguous and worldwide the NEC incidence is constant or increasing ( 19 , 21 ).…”
Section: Introductionmentioning
confidence: 99%